Effectiveness Of The School Procurement Information System (SIPLah) In Procurement Of Goods And Services In Public Schools - Salsabila, Aniqah; Wahyu Sri Ambar Arum; Neti Karnati (Asosiasi Asesmen Pendidikan (AAP), 2024)
SIPLah is an innovation designed to streamline the procurement of goods and services in schools, ensuring efficiency, transparency, and accountability. This research evaluates the effectiveness of the School Procurement Information System (SIPLah) at SMPN 14 Bekasi using a qualitative approach and descriptive methods, including observation, documentation, and interviews. The study analyzes planning, implementation, supervision, and the impact of SIPLah, as well as its effectiveness in financing. Findings indicate that SIPLah enhances the procurement process by improving efficiency, transparency, and accountability, speeding up transactions, and reducing errors. It also facilitates online financing with transparency and minimizes fund misuse. Despite occasional technical issues, SIPLah is 90% effective in terms of process, impact, financing, and system usage, meeting principles such as flexibility, efficiency, accessibility, security, and speed.